Magnetic and Dielectric Properties of La and Ni Co-substituted BiFeO3 Nanoceramics - Srivastava, Amit; Singh, Ashwani Kumar; Srivastava, O. N.; Tewari, H. S.; Masood, Khalid B.; Singh, Jai (Frontiers in Physics, 2020)
The increasing plead for the realization of ultra-fast, miniaturized, compact, and ultra-low power consumption in electronic as well as spintronic devices has propelled the quest for novel multiferroic materials that efficiently enable voltage control of magnetism. The present work reports the phase stability, magnetic and dielectric responses of polycrystalline Bi1−xLaxFe1−yNiyO3 (0 ≤ x ≥ 0.2 and 0 ≤ y ≥ 0.2) multiferroic ceramics synthesized through a simplistic sol–gel approach. The maneuver substitutions of La at A− site of BiFeO3 multiferroic eliminate the secondary phases formed owing to impurities. Rietveld refined XRD analysis reveals the structural transformation of the orthorhombic (Pbnm) phase as La substitution increases. However, an additional lattice distortion is induced as a result of the substitutions of Ni atoms at B− site. A substantial enhancement in magnetic and dielectric responses has been found in the co-doped (Ni and La) sample at both A and B− sites as a result of the size confinement of nano-crystallites, the exchange interaction between Fe3+ and Ni2+ ions, and corresponding variation in Fe–O–Fe bond angles. The dielectric constant has increased substantially in the low-frequency region with simultaneous substitutions of La and Ni at the sites of Bi and Fe, respectively. A careful observation of temperature-dependent magnetization curves (FC and ZFC) indicates a spin glass response with entangled ferromagnetic components. The experimental findings infer that the co-substitutions of La and Ni at their respective sites in Bi1−xLaxFe1−yNiyO3 (0 ≤ x ≥ 0.2 and 0 ≤ y ≥ 0.2) may significantly improve the ferromagnetic and dielectric responses of the studied nanoceramics.